The Pragmatics of Greetings Reflected in the Textbooks for Teaching English as a Foreign Language in Indonesia - Inawati, Iin (Universitas Ahmad Dahlan, 2016)
This article reports on the finding of a study which aims to analyze the pragmatic content of nine school textbooks intended for use in Indonesian secondary schools. Specifically, the article examines how greetings are linguistically presented in the textbooks and whether adequate meta-pragmatic information is provided to facilitate the learning of the greetings. The analysis shows that less various types of greetings are presented in the textbook and meta-pragmatic information is limited. It is suggested for teacher and textbooks writers to reconsider the types of instructional materials that can most effectively prepare learners for communication in a wider and more diverse world.Keyword:Â textbooks, greetings, meta-pragmatic